2020
DOI: 10.1016/j.eneco.2020.104776
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the role of the exchange rate in oil-related scenarios for the European stock market

Abstract: This paper should not be reported as representing the views of the European Central Bank (ECB). The views expressed are those of the authors and do not necessarily reflect those of the ECB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The long-term correlation between exchange rates and oil prices, along with their influencing factors, was evaluated by Yang et al (2018) using dynamic conditional correlation-mixed data sampling (DCC-MIDAS) on the exchange rates of Japan, Canada, Germany, and Eurozone-based USD and crude oil data. According to Ferreiro (2020), the issue in the literature lies in how the stock market responds to a distressed scenario caused by oil prices in the local currency. To address this, he proposed creating an oil-related scenario that takes into account the source of risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The long-term correlation between exchange rates and oil prices, along with their influencing factors, was evaluated by Yang et al (2018) using dynamic conditional correlation-mixed data sampling (DCC-MIDAS) on the exchange rates of Japan, Canada, Germany, and Eurozone-based USD and crude oil data. According to Ferreiro (2020), the issue in the literature lies in how the stock market responds to a distressed scenario caused by oil prices in the local currency. To address this, he proposed creating an oil-related scenario that takes into account the source of risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argued that stock market irregularities are more significant as oil prices rise due to increased demand for the resource since returns associated with anomalies indicate market manipulation. A study done by Ferreiro [47] showed losses due to the decrease in oil price in U.S. dollars and, on the contrary, gains for oil prices in euros highlighted the impact of exchange rate on global markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most recent literature on this topic uses copula theory to show the increasing co-movement between the commodity and equity markets (Ojeda, 2020;Tiwari et al 2020, Aepli et al 2017.…”
Section: Introductionmentioning
confidence: 99%